2008
DOI: 10.1037/0033-295x.115.2.463
|View full text |Cite
|
Sign up to set email alerts
|

New paradoxes of risky decision making.

Abstract: During the last 25 years, prospect theory and its successor, cumulative prospect theory, replaced expected utility as the dominant descriptive theories of risky decision making. Although these models account for the original Allais paradoxes, 11 new paradoxes show where prospect theories lead to self-contradiction or systematic false predictions. The new findings are consistent with and, in several cases, were predicted in advance by simple "configural weight" models in which probability-consequence branches a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
393
4
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 343 publications
(412 citation statements)
references
References 192 publications
(530 reference statements)
14
393
4
1
Order By: Relevance
“…Additionally, the strength of preference between 330 monetary outcomes seems to be taken into account by the subjects, and axioms that prevent rankings to be based on average-goodness were violated on a large scale. 6 All of these findings are compatible with UEU and thus constitute evidence in favour of the criterion. Yet, we also found that under particular circumstances, people appear to prefer sets that are obviously less attractive in 335 terms of the arithmetic mean over the outcomes, which can only be explained by UEU if an extremely risk averse utility function is assumed.…”
Section: Discussion Of the Experimentssupporting
confidence: 70%
“…Additionally, the strength of preference between 330 monetary outcomes seems to be taken into account by the subjects, and axioms that prevent rankings to be based on average-goodness were violated on a large scale. 6 All of these findings are compatible with UEU and thus constitute evidence in favour of the criterion. Yet, we also found that under particular circumstances, people appear to prefer sets that are obviously less attractive in 335 terms of the arithmetic mean over the outcomes, which can only be explained by UEU if an extremely risk averse utility function is assumed.…”
Section: Discussion Of the Experimentssupporting
confidence: 70%
“…in Table 1); and Birnbaum (2008) documented a splitting effect (splitting a possible outcome into two less desirable outcomes can increase its attractiveness; see Row 10 in Table 1). …”
Section: Classical Demonstration Current Replicationmentioning
confidence: 99%
“…Our analysis of this tendency, summarized in Figure The splitting effect. Studies of decisions under risk show that splitting an attractive outcome into two distinct outcomes can increase the attractiveness of a prospect even when it reduces its expected value (see Birnbaum, 2008;Tversky & Kahneman, 1986; and see Row 10 in Table 1). Figure 9 summarizes our effort to replicate this effect in our paradigm.…”
Section: The Reflection and Reversed Reflection Effects A Comparisonmentioning
confidence: 99%
“…This model has three adjustable parameters and is a special case of the more general configural weight model (Birnbaum, 2004). Like prospect theory, the transfer of attention exchange model emphasizes how choice problems are described and presented to people.…”
Section: The Contestantsmentioning
confidence: 99%